Validating Model of Travellers’ Intention to Revisit of an Islamic Destination via Consistency Partial Least Square (PLSc) - Mohd Hanafi Azman Ong; Rasidah Hamid; Muhamad Addin Burhanuddin; Wan Nazriah Wan Nawawi; Noorazlin Ramli (International Journal of Supply Chain Management, 2019)
The purpose of this study is to validate the links among factor influencing tourists to revisit of an Islamic destination towards Muslim amenities and lifestyle, cognitive destination image and quality of service on a traveller’s intention to revisit Islamic tourism destination. All the data was being collected using a self-administered approach questionnaire. The influencing factors of tourists to revisit are being validated by using the Consistency Partial Least Square (PLSc) via Structural Equation Modelling (SEM) technique. The findings indicated that, the purposed model were valid to modelling the travellers’ intention since the SRMR and NFI indices were meet the minimum requirement of the analysis. Besides that, Muslim-Friendly Amenities and Lifestyle, Cognitive Image, and Service Quality having a simultaneously positive significant effect toward Intention to Revisit. It is indicated that, Islamic tourism should be acknowledge of the importance of Muslim amenities and lifestyles, cognitive destination image and quality of services in keep tourists to revisit